Optimizing Customer Engagement and Satisfaction on Loyalty through Self-Congruity Theory - Solekhah, Amira Alda Arisani; Marsasi, Endy Gunanto (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study explores the factors that shape the intention of Generation Z, aged 20 to 29, in Java to utilize online travel agents. Additionally, it investigates the application of self-congruity theory in understanding consumer behavior. A unique aspect of this research is the inclusion of a novel variable: satisfaction.Design/Methodology/Approach: This research adopts a quantitative approach, utilizing a survey method to gather insights. The data analysis was performed using Structural Equation Modeling (S.E.M.), drawing on responses from 198 participants. The study specifically focuses on Generation Z as its primary subject.Research Findings: This study found that self-congruity influences customer trust and customer engagement, which ultimately contributes to the satisfaction and loyalty of online travel agent users. The satisfaction variable highlights its crucial role in reinforcing the connection between customer engagement and loyalty.Theoretical Contribution/Originality: This study enriches the academic literature by adding the satisfaction variable as a novelty and highlights the critical role of self-concept and trust in building customer loyalty.Practitioners/Policy Implications: To increase loyalty, online travel agent companies must align their brand image with consumers' self-concept, build trust through consistent service, and manage customer engagement wisely.Research Limitations/Implications: This research is limited by fewer samples, the uneven distribution of respondents, and the geographical coverage only on the island of Java.